Surfaces by vibration/modulation-assisted texturing for tribological applications. Issue 1 (July 2016) - Gandhi, R.; Sebastian, D.; Basu, S.; Mann, J.; Iglesias, P.; Saldana, C.
Abstract Various micro-scale surface texturing techniques have been used to control surface topography; however, conventional protocols are inherently difficult to adapt in large surface area applications. Micro-scale material removal methods based on superimposed tool modulation offer advantages for overcoming this challenge through direct-write processing. In this study, the ability to prescribe micro-scale textures of controlled size and morphology by control of underlying process parameters in vibration/modulation-assisted machining is demonstrated. Novel surface textures including protrusions (ribs and fins) and depressions (dimples) were generated, and corresponding geometric surface models were developed. The tribological performance of dimple-type textures was characterized by lubricated ball-on-flat wear testing. The dimple-type surface textures resulted in a substantial reduction in wear factor for two material systems, brass and an aluminum alloy. The effect of the texturing process on surface and subsurface microstructure was measured using electron microscopy. Heterogeneities in crystallographic texture and grain size along the textured surface were linked to local variations in machining conditions during surface generation.